Enhanced Oil Recovery Selected Topics - Morsi, Badie I.; Baled, Hseen O. (IntechOpen, 2022)
Enhanced Oil Recovery - Selected Topics includes nine chapters in five sections. Chapters address enhanced oil recovery (EOR) processes, such as miscible flooding, surfactants flooding, polymers flooding, and microbial flooding. They also present fundamental and technical details along with case studies. This book provides ample and useful knowledge for the design of laboratory-scale and field-scale EOR processes. It is a useful resource for practitioners working in oil field production applications and graduate students pursuing advanced degrees in petroleum engineering.